Wage Differentials in the 1990s in Israel : Endowments, Discrimination, and Selectivity - Shoshana Neuman; Ronald L. Oaxaca (Institute for the Study of Labor (IZA), 2004)
The purpose of this paper is to investigate wage structures of professional workers in the Israeli labor market, using data from the most recent 1995 Census and correcting for selectivity at the stage of entrance into the occupation. The sample of professionals is decomposed into several subsamples: men and women and within each gender a distinction is made between Easterners (origination from Asian/African countries) and Westerners (from European/American countries of origin). Comparisons by gender and ethnicity can then be made. Characteristics (endowments) and wage structures of the four groups are presented. Wage equations include the Inverse of Mill's Ratio as a regressor to correct for selection into the professional occupations. Wage differences are then examined and decomposed into 3 components: Endowments (human capital), discrimination and selectivity. Following the methodology presented in Neuman and Oaxaca (2004), four alternative decompositions are suggested and discussed.
Keywords: J44; J71; J31; J16; J15; 330; endowments; discrimination; selectivity; gender; ethnicity; Israel; Lohnstruktur; Lohndifferenzierung; Lebensalter; Geschlecht; Ethnische Gruppe; Bildungsniveau; Israel